Organisational resilience building in Small and Micro Enterprises under the VUCA environment - You, Yue; Latada , Fatmawati; Zhang, Ziran (Journal of Islamic, Social, Economics and Development, 2025)
Small and micro enterprises (SMEs) encounter big blows while operating in VUCA (Volatility, Uncertainty, Complexity, Ambiguity) environment as a result of their resource constrains and external dependencies. This study build a conceptual model that links organized performance to the elements of external environmental factors, internal resources, resilience capabilities, and the contribution of resilience building to SMEs. From systematically reviewing literature on VUCA and organisational resilience theories, the model specifies the pathways of how SMEs adapt and thrive in continuously changing (VUCA) conditions.